PENGARUH EXPERIENCE ECONOMY TERHADAP VIVID MEMORY DAN LOYALTY FESTIVAL PARADE BUDAYA DAN PAWAI BUNGA DI SURABAYA - Erna Andajani; Lindya Aqmarina Ghaisani; Siti Rahayu (Master of Management, Mataram University, 2019)
This study aimed to examine the effect of Experience Economy (Education Experience, Entertainment Experience, Escapism Experience, dan Esthetics Experience) on Vivid Memory and Loyalty Festival. This study used sample of 200 respondents. This research used quantitative approach through statistical test. Data analysis Method that used in this research was SEM (Structural Equation Modeling). The results of this study indicated that Experience Economy (Education Experience, Entertainment Experience, Escapism Experience, and Esthetics Experience) proved to have a positif significant effect on Vivid Memory visitors of the Parade Budaya dan Pawai Bunga Surabaya. However loyalty was affected only by the Entertainment Experience and Esthetics Experience. Penelitian ini bertujuan menguji pengaruh Experience Economy (Education Experience, Entertainment Experience, Escapism Experience, dan Esthetics Experience) terhadap Vivid Memory dan Loyalty Festival. Objek yang digunakan dalam penelitian ini adalah Parade Budaya dan Pawai Bunga Surabaya. Penelitian ini menggunakan sampel sebanyak 200 responden. Penelitian ini menggunakan pendekatan kuantitatif melalui pengujian secara statistik. Metode analisis data yang digunakan dalam penelitian ini adalah SEM (Structural Equation Modeling).vHasil penelitian ini menunjukkan bahwa Experience Economy(Education Experience, Entertainment Experience, Escapism Experience, dan Esthetics Experience) secara signifikan berpengaruh positif terhadap Vivid Memory pengunjungParade Budaya dan Pawai Bunga Surabaya, Namun Loyalty hanya dipengaruhi oleh Entertainment Experience dan Estethics Experience.Keywords : Experience Economy, Vivid Memory, Loyalty